A Composite Polymeric Carbon Nitride with In Situ Formed Isotype Heterojunctions for Highly Improved Photocatalysis under Visible Light. Issue 9 (9th December 2016) - Liang, Qinghua; Li, Zhi; Bai, Yu; Huang, Zheng‐Hong; Kang, Feiyu; Yang, Quan‐Hong
Abstract : Introducing heterojunction is an effective way for improving the intrinsic photocatalytic activity of a graphitic carbon nitride (GCN) semiconductor. These heterostructures are mostly introduced by interfacing GCN with foreign materials that normally have entirely different physicochemical properties and show unfavorable compatibility, thus resulting in a limited improvement of the photocatalytic performance of the resultant materials. Herein, a composite polymeric carbon nitride (CPCN) that contains both melon‐based GCN and triazine‐based crystalline carbon nitride (CCN) is prepared by a simple thermal reaction between lithium chloride and GCN. Thanks to the intimate contact and good compatibility between GCN and CCN, an in situ formed heterojunction acts as a driving force for separating the photogenerated charge carriers in CPCN. As a result, CPCN exhibits a significantly improved photocatalytic performance under visible light irradiation, which is, respectively, 10.6 and 5.3 times as high as those of the GCN and CCN alone. This well designed isotype heterojunction by a coupling of CCN presents an effective avenue for developing efficient GCN photocatalysts. Abstract : A heterostructural composite polymeric carbon nitride that contains both melon‐based graphitic carbon nitride and triazine‐based crystalline carbon nitride exhibits a significantly improved photocatalytic performance under visible light irradiation.